Predictors of police harassment and arrests among homeless and runaway adolescents - Thrane, Lisa Ellen (2003)
This study examines risk factors associated with informal and formal contact with law enforcement among 602 homeless and runaway youth from the Midwest. This study considers the effects of extra-legal factors, family context, individual traits, and situational considerations on the frequency of police harassment and self-reported post-runaway arrests. In addition, potential interactions will be examined. In the final model, the findings reveal that males are more likely to be hassled by the police. Youth Self-Report (YSR) aggressive behavior is a subscale from Achenbach's Youth Self-Report (1991) Externalizing behavior. It is positively associated with police harassment. Deviant subsistence strategies and drug use exert a strong influence on the independent variable. In addition, older Black adolescents are more likely to be hassled than their White counterparts. In the final analysis of post-runaway arrests, age is statistically significant. Paternal crime increases adolescents' self-reported arrests after running away from home. A prior arrest and aggressive behavior increase the risk for formal contact with police. Younger-aged runaways report more arrests. The length of time spent on the street has a similar effect. Deviance and drug use positively influence arrests. Younger-aged runaways who employed high levels of deviance report the most arrests. This study suggests that involvement with the justice system is not simply the result of deviant behavior or individual and family level factors. Extralegal factors and the visibility of being on the street also shape encounters with the police. This paper underscores the need to conduct research at various stages of the justice system